Implementasi Marketing Mix 7P. Studi Kasus pada Klinik Universitas Brawijaya - Ulfa, Dina Maria; Enjelika, Enjelika; Romadhoni, Satrio Ahmadtul Firdaus; Sudarmiatin, Sudarmiatin (Journal of Management and Bussines (JOMB), 2025)
This study aims to analyze the implementation of the Marketing Mix 7P strategy at Universitas Brawijaya Clinic (Klinik UB) to enhance competitiveness and patient satisfaction. The strategy encompasses the elements of Product, Price, Place, Promotion, People, Process, and Physical Evidence, applied holistically to create an optimal service experience. The research employs a qualitative descriptive method through in-depth interviews and direct observation. The results indicate that Klinik UB successfully integrates the Marketing Mix 7P elements to expand service accessibility, improve service quality, and strengthen patient trust. This study provides insights into the importance of comprehensive marketing strategies in addressing competition in the healthcare sector. Keywords: Marketing Mix 7P, marketing strategy, patient satisfaction, healthcare clinic, competitiveness